2022
DOI: 10.24843/jbiounud.2022.v26.i01.p02
|View full text |Cite
|
Sign up to set email alerts
|

Kandungan alkaloid dan flavonoid tiga spesies anggrek berpotensi obat dari Kawasan Gunung Gumitir Kabupaten Jember

Abstract: Tumbuhan anggrek dikenal sebagai tumbuhan hias, selain itu juga berpotensi sebagai obat diantaranya adalah Dendrobium linearifolium Teijs & Binn., Bulbophyllum odoratum (Blume) Lindl., dan Vanda tricolor Lindl. Khasiat obat pada tumbuhan adalah karena adanya metabolit sekunder, antara lain alkaloid dan flavonoid. Penelitian ini bertujuan untuk menentukan kandungan alkaloid dan flavonoid pada tiga spesies anggrek berpotensi obat dari kawasan Gunung Gumitir Kabupaten Jember. Sampel ketiga spesies anggrek dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Therefore, fungal growth was still present around the inhibition zone as fungistatic substances only inhibit the fungi growth without killing the cells [17][18]. According to Setyati et al, D. linearifoilum leaves contain alkaloids and flavonoids [13]. Alkaloid compounds inhibit the function of the fungal cell's genetic material by inhibiting DNA formation, topoisomerase, and membrane synthesis, as explained by Sulaiman et al [19].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, fungal growth was still present around the inhibition zone as fungistatic substances only inhibit the fungi growth without killing the cells [17][18]. According to Setyati et al, D. linearifoilum leaves contain alkaloids and flavonoids [13]. Alkaloid compounds inhibit the function of the fungal cell's genetic material by inhibiting DNA formation, topoisomerase, and membrane synthesis, as explained by Sulaiman et al [19].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…According to Sujarwo and Lestari (2018), the pseudobulb of D. linearifolium in the Hindu community in Bali has been used as a medicine for earache by dripping water stored in the pseudobulb and the orchid has been used as a medicinal ingredient to prevent infections in the ear canal [12]. The secondary metabolite content detected in all parts of this plant in the form of alkaloids and flavonoids has been reported with the highest content found in the leaves [13]. The DNA barcode with ITS2 marker dah been reported elsewhere [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study reported the secondary metabolites of alkaloid and flavonoid content of wild orchids from the Mount Gumitir area (Setyati et al, 2022). Liparis resupinata Ridl.…”
Section: Introductionmentioning
confidence: 99%